Purposeful Entanglements: A New Materialist Analysis of Transformative Interviews - Marn, Travis M.; Wolgemuth, Jennifer R. (Qualitative Inquiry, 2017)
In this article, we explore transformative interviewing through the lens of new materialism. Rather than viewing transformation through a humanist perspective that centralizes a transcendent self, we draw upon Barad’s agential realism to reconsider transformation following the ontological turn. Thinking with agential realism, we engaged two interview studies, one on biracialism and one on masculinity, to demonstrate how the materiality of our interviews (e.g., research bodies, computer programs, questionnaires) intra-acted with our participants to both facilitate and hinder our attempts at transformation. We conclude by theorizing transformation as a type of purposeful entanglement that proceeds from the material-discursive intra-actions of our inquiries.
Keywords: dept.cur

Start here, or here, no here: introductions to rethinking education policy and methodology in a post-truth era - Wolgemuth, Jennifer R.; Koro-Ljungberg, Mirka; Marn, Travis M.; Onwuegbuzie, Anthony J.; Dougherty, Shaun M. (Education Policy Analysis Archives, 2018)
This special issue takes up urgent questions about how we education scholars might think and do policy and methodology in what has come to be known as the post-truth era. The authors in this special issue grapple with questions about the roles and responsibilities of educational researchers in an era in which research and policy have lost their moorings in T/truth. Collectively they reconceptualize educational research and policy in light of post-truths, anti-science sentiment, and the global rise of right-wing populism. At the same time we editors wonder whether post-truth is given a bad rap. Could post-truth have something productive to offer? What does post-truth open up for educational research and policy? Or, is the real issue of this special issue a collective despair of our own insignificance and obsolescence in the wake of post-truth. Whatever we editors and authors aimed to do, this special issue will not be heard by post-truth adherents and partisans. Perhaps its only contribution is encouragement to stay with the troubles of a post-truth era, even as we despair the consequences of our research and policy creations. © 2018, Arizona State University. All rights reserved.
6 citations (Crossref) [2023-10-31] Citation Key Alias: pop00129 tex.type: [object Object]
Keywords: Education policy; Fake news; Methodology; Post-truth; dept.cur; peer-reviewed

Work/Think/Play/Birth/Death/Terror/Qualitative/Research - Wolgemuth, Jennifer R.; Rautio, Pauliina; Koro-Ljungberg, Mirka; Marn, Travis M.; Nordstrom, Susan; Clark, Adam (Qualitative Inquiry, 2018)
Inspired by work/think/play in qualitative research, we centered the idea of “play” in a qualitative research project to explore what proceeding from the idea of work/think/play might look like and accomplish. We pursued play in an experimental qualitative inquiry over dinner one night at the 2016 Annual Meeting of the American Educational Research Association. Our article centers on one work/think/play inquiry three of us conducted. Through a playful account of how play unfolded in our work/think/play inquiry that evening, we explore research play as generative, deadly, and censored in the context of neoliberalism and other terrors. We reflect on what (good) play does in qualitative research, what our work/think/play/birth/death/terror/qualitative/research accomplished, if anything. Maybe research play is vital, what keeps us fit to do critical qualitative research. Yet research play moves (well) beyond normative rules of much qualitative research. Is it worth the risk? Can we know? Even after?
Keywords: dept.cur